2005
DOI: 10.1080/02713680591005922
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety of GDNF Gene Delivery in the Retina

Abstract: Long-term expression of GDNF within the eyes can be achieved by intravitreal injection of rAAV vectors in the absence of morphological or functional deficits in the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Following the concerns regarding the suppression of retinal function caused by CNTF, it has been demonstrated that AAV-mediated GDNF expression does not result in a reduction in normal retinal function; wild-type mice treated in one eye with highdose AAV.GDNF show no reduction in ERG b-wave amplitudes or waveform when compared with untreated eyes . This result confirms the findings of a previous study in rats, where long-term safety of AAVmediated GDNF expression was demonstrated by histology and electroretinography [Wu et al, 2005]. These studies demonstrate the potential of GDNF as a neuroprotective agent for retinal gene therapy.…”
Section: Strategies For Long-term Neuropro-tection -Gdnf As a Candidasupporting
confidence: 93%
“…Following the concerns regarding the suppression of retinal function caused by CNTF, it has been demonstrated that AAV-mediated GDNF expression does not result in a reduction in normal retinal function; wild-type mice treated in one eye with highdose AAV.GDNF show no reduction in ERG b-wave amplitudes or waveform when compared with untreated eyes . This result confirms the findings of a previous study in rats, where long-term safety of AAVmediated GDNF expression was demonstrated by histology and electroretinography [Wu et al, 2005]. These studies demonstrate the potential of GDNF as a neuroprotective agent for retinal gene therapy.…”
Section: Strategies For Long-term Neuropro-tection -Gdnf As a Candidasupporting
confidence: 93%
“…At >2.5 ng/ml, these hGDNF levels are nearly tenfold higher than those produced in previous studies that have achieved photoreceptor degeneration rescue through GDNF overexpression from retinal neurons after subretinal injection 9,10 or from intraocularly placed mouse embryonic stem cells. 15 Importantly, the expression is sustained, as ELISA measurements of GDNF in the vitreous of rats 5 months postinjection show elevated levels of the therapeutic protein (Supplementary Figure S2), which are both safe 21 and necessary for sustained rescue.…”
Section: Introductionmentioning
confidence: 94%
“…65,66 Whether similar negative effects on retinal histology and function would be observed in other model of RP or in normal rat eyes, remains to be determined. To date, analyses performed 7 days after IVT injection of 100 ng GDNF in the pig, 37 8 weeks after subretinal administration of recombinant adeno-associated virus --GDNF in the mouse 11 or 1 year after IVT administration or recombinant adeno-associated virus --GDNF in the rat 67 did not mention any sign of ocular toxicity or visual function disturbances in healthy eyes. GDNF was also well tolerated in several animal models of retinal pathology (see Table 1).…”
Section: Discussionmentioning
confidence: 99%